Public preferences for the improvement of existing piped water provision: a choice experiment in Sri Lanka - Rajapakshe, Prasanna Sisira Kumara; Termansen, Mette; Paavola, Jouni (Frontiers in Water, 2023)
Lack of access to good quality water, unsustainable use and health impacts related to unsafe water are considerable challenges to water resource management and are a central public policy issue in many developing countries. Today the challenge of improving water service in developing countries is does not only lie with provision of new connections for the households who are depending on non-piped sources, but also to enhance the service level of the existing networks to meet people’s expectations. A choice experiment is applied to estimate the benefits of service improvements of piped water supply schemes in terms of water quality, reliability, pressure level, management organization. The empirical research was carried out in Sri Lanka, and included a survey of 307 households with piped-borne water supply served by over 20 water supply systems managed by governmental organisation and CBOs. The results indicate that households are willing to pay substantial amounts for water service improvements, particularly for the improvement of water quality. The Latent Class and Random Parameter Logit model results reveal that there are significant preference heterogeneity regarding water service improvements. Therefore, policy initiatives relying on household financing need to be evaluated for the cost/benefit effects across diverse classes of households.